Impact of green synthesized selenium nanoparticles on the growth and development of amaranth microgreens - Gomathi, Arivalagan; Sriharini, Ramalingam; Arumuka Pravin, Iyadurai; Kaushik, Rajaram; Ramesh Kumar, Alagarsamy; Anbu Sezhian, Ambethgar; Srivignesh, Sundaresan (Frontiers in Nanotechnology, 2025)
Drought stress is a prime abiotic constraint that reduces microgreen growth and nutritional quality. This research explores a new strategy involving using green-synthesized selenium nanoparticles (SeNPs) to improve drought stress tolerance and biofortification of Amaranthus microgreens (var. Arka Suguna). SeNPs were synthesized from Cassia auriculata leaf extract and characterized via UV-Vis spectroscopy, TEM, XRD, FT-IR, and DLS, establishing their crystalline nature, spherical shape (80.6–135 nm), and phytochemical capping. Toxicity screening indicated 1,000 ppm as growth-inhibitory, whereas 100 ppm was optimal for plant growth. Drought assays employing PEG-induced stress indicated that 100 ppm SeNPs greatly enhanced germination (97.5%), yield (330 mg), plant height (5.6 cm), and biochemical profiles. Treated microgreens exhibited higher total protein (377.2 mg/100 g), carbohydrates (951 mg/100 g), flavonoids (11.4 mg/g), vitamin C (36.67 mg/100 g), and antioxidant enzyme activities (SOD: 0.065 U/mg/min; CAT: 13.5 U/mg/min). SeNPs also promoted selenium accumulation (10.69 mg/g DW) and had no negative impacts on valuable soil microbes, including Pseudomonas aeruginosa, Bacillus subtilis, and Trichoderma viride. This paper is the first comprehensive report on Cassia auriculata-mediated SeNPs administered through seed, soil, and foliar application to enhance drought tolerance and nutrient status in Amaranth microgreens. The findings indicate SeNPs as a green nano-priming approach for promoting crop yield under abiotic stress conditions.